Characterization of the 5′-flanking region of the human and mouse CHAC1 genes - Nomura, Yuki (Biochem Biophys Rep, 2020)
The Unfolded Protein Response pathway is a conserved signaling mechanism having important roles in cellular physiology and is perturbed accompanying disease. We previously identified the novel UPR target gene CHAC1, a direct target of ATF4, downstream of PERK-EIF2A and activated by the UPR pathway. CHAC1 enzyme directs catalysis of γ-linked glutamate bonds within specific molecular targets. CHAC1 is the first enzyme characterized that can catalyze intracellular glutathione degradation in eukaryotes, having implications for regulation of oxidative stress. DDIT3 (CHOP) is a terminal UPR transcription factor, regulated by ATF4 and an output promoting cell death signaling. Herein we examine the relationship of CHOP controlling CHAC1 transcription in humans and mice. We note parallel induction of CHOP and CHAC1 in human cells after agonist induced UPR. Expanding upon previous reports, we define transcriptional induction of CHAC1 in humans and mice driven by ATF4 through a synergistic relationship with conserved ATF/CRE and CARE DNA sequences of the CHAC1 promoter. Using this system, we also tested effects of CHOP on CHAC1 transcription, and binding at the CHAC1 ATF/CRE using IM-EMSA. These data indicate a novel inhibitory effect of CHOP on CHAC1 transcription, which was ablated in the absence of the ATF/CRE control element. While direct binding of ATF4 to CHAC1 promoter sequences was confirmed, binding of CHOP to the CHAC1 ATF/CRE was not evident at baseline or after UPR induction. These data reveal CHAC1 as a novel CHOP inhibited target gene, acting through an upstream ATF/CRE motif via an indirect mechanism.